2018
DOI: 10.2217/cer-2017-0086
|View full text |Cite
|
Sign up to set email alerts
|

Front-line treatment of patients with chronic lymphocytic leukemia: a systematic review and network meta-analysis

Abstract: Aim:A systematic literature review and network meta-analysis were conducted to determine the relative efficacy and safety of interventions for treatment-naive chronic lymphocytic leukemia patients, as comparative evidence is scarce. Materials & methods: Relative treatment effects of progression-free survival, overall survival and safety outcomes were estimated via network meta-analysis based on data identified via systematic literature review. Results: Ibrutinib was superior in all pairwise comparisons for pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…These findings are consistent with the results of a previously conducted network meta‐analysis of 15 randomized controlled trials in the first‐line CLL setting, including ibrutinib data from the primary analysis of the RESONATE‐2 study (median follow‐up 18.4 months) . Results of the network meta‐analysis demonstrated a benefit in PFS, as well as OS, with ibrutinib over CIT in overall and fludarabine‐ineligible populations, with particular efficacy demonstrated in subgroups with del(11q) or unmutated IGHV statu s .…”
Section: Discussionsupporting
confidence: 87%
“…These findings are consistent with the results of a previously conducted network meta‐analysis of 15 randomized controlled trials in the first‐line CLL setting, including ibrutinib data from the primary analysis of the RESONATE‐2 study (median follow‐up 18.4 months) . Results of the network meta‐analysis demonstrated a benefit in PFS, as well as OS, with ibrutinib over CIT in overall and fludarabine‐ineligible populations, with particular efficacy demonstrated in subgroups with del(11q) or unmutated IGHV statu s .…”
Section: Discussionsupporting
confidence: 87%
“…10,[26][27][28] A recent network meta-analysis of randomized clinical trials showed superior benefit in survival and safety with ibrutinib compared with other first-line treatments for CLL. 29 According to the network metaanalysis of safety outcomes, ibrutinib was associated with the lowest risk of treatment discontinuations and discontinuations due to AEs vs comparators in the overall first-line population and the fludarabine-ineligible population. 29 Of note, higher discontinuation due to toxicity has been reported with ibrutinib outside of the clinical study setting.…”
Section: Discussionmentioning
confidence: 99%
“…29 According to the network metaanalysis of safety outcomes, ibrutinib was associated with the lowest risk of treatment discontinuations and discontinuations due to AEs vs comparators in the overall first-line population and the fludarabine-ineligible population. 29 Of note, higher discontinuation due to toxicity has been reported with ibrutinib outside of the clinical study setting. 30 Such variations in discontinuation rates between "real-world" and clinical studies are likely due to differences in patient and study characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…This clear benefit in overall survival and long-term safety outcomes was also described in a network meta-analysis 17. Ibrutinib has the lowest risk of treatment discontinuations owing to less frequent adverse events 17. In addition, ibrutinib-treated patients may have their bone marrow function restored 18.…”
Section: Discussionmentioning
confidence: 77%
“…The randomised phase 3 studies (RESONATE-2 trial) provides an extensive clinical evidence supporting the superiority of monotherapy ibrutinib in newly diagnosed older patients with CLL compared with chlorambucil, which is a standard first-line cytotoxic chemotherapy 16. This clear benefit in overall survival and long-term safety outcomes was also described in a network meta-analysis 17. Ibrutinib has the lowest risk of treatment discontinuations owing to less frequent adverse events 17.…”
Section: Discussionmentioning
confidence: 96%